On the Steric Sea Level in the Red Sea - Abdallah, A. M.; Eid, F. M. (The International Hydrographic Review, 2015)
Thermal, haline and total steric departures from mean sea level were calculated during winter and summer seasons in six regions representing the whole area of the Red Sea. Thermal and haline components of steric departure are in phase in most regions, although they have different contributions to the total steric departure. The steric sea level in the southern regions of the sea is higher than that in the northern parts by estimated values of about 19 cm in winter and 23 cm in summer. Across the sea, the changes in steric sea level are clearly observed in winter due to the relatively complex circulation pattern characterizing that season. The steric factor is considered to be one of the controlling factors that affect sea level fluctuations in the northern Red Sea during the summer season and in the southern regions in winter.